Исследования Малополовецкого археологического комплекса в 2009 г. - Лысенко, С.Д.; Лысенко, С.С.; Литвинова, Л.В. (Археологічні дослідження в Україні, 2010)
In 2009, Fastiv Archaeological Expedition uncovered 212 m2 and studied seven graves of the Bronze and the Early Iron Ages, and the Ancient Rus period (185—191) at Malopolovetske 3 burial ground. A detailed survey of the surface at Malopolovetske 2Д settlement was conducted; finds are represented by ceramics of Bilohrudiv and Mylohrad types, Chernyakhivska culture, the Ancient Rus and the Late Mediaeval periods.